Enhancing expression of SSU1 genes in Saccharomyces uvarum leads to an increase in sulfite tolerance and a transcriptome profile change. Issue 3 (25th April 2017) - Liu, XZ; Sang, M; Zhang, XA; Zhang, TK; Zhang, HY; He, X; Li, SX; Sun, XD; Zhang, ZM
Abstract: Saccharomyces uvarum is a good wine yeast species that may have great potential for the future. However, sulfur tolerance of most S. uvarum strains is very poor. In addition there is still little information about the SSU1 gene of S. uvarum, which encodes a putative transporter conferring sulfite tolerance. In order to analyze the function of the SSU1 gene, two expression vectors that contained different SSU1 genes were constructed and transferred into a sulfite-tolerant S. uvarum strain, A9. Then sulfite tolerance, SO2 production, and PCR, sequencing, RT-qPCR and transcriptome analyses were used to access the function of the S. uvarum SSU1 gene. Our results illustrated that enhancing expression of the SSU1 gene can promote sulfite resistance in S. uvarum, and an insertion fragment ahead of the additional SSU1 gene, as seen in some alleles, could affect the expression of other genes and the sulfite tolerance level of S. uvarum . This is the first report on enhancing the expression of the SSU1 gene of S. uvarum . Abstract : Enhanced expression of the SSU1 gene promotes sulfite resistance in Saccharomyces uvarum, and an insertion of a DNA fragment upstream of an additional copy of the SSU1 gene affects the expression of other genes and the sulfite tolerance level of S. uvarum .